Analysis of Initial Profiles of Students' Creative Thinking Skills in Biology Learning - Widiyaningsih, Tutut; Adi Prayitno, Baskoro; Indrowati, Meti (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2026)
This study aims to analyze the initial profile of high school students' creative thinking skills in biology learning. The research is descriptive quantitative research using an open-ended test method. The subjects of this study were tenth-grade high school students. The results of the analysis show that the average creative thinking skills of high school students is 37.85%, which is classified as not creative. Specifically, the lowest percentages were found in the aspects of originality, elaboration, and flexibility, while the aspect of fluency showed relatively higher achievements. The conclusion of this study is that the profile of students' creative thinking skills in biology learning is low. These findings indicate that the dominance of convergent learning through closed questions and student passivity in class are factors that inhibit the development of divergent thinking potential. Therefore, it is necessary to apply active learning models and use more exploratory evaluation instruments to stimulate students' ability to produce unique, flexible, and in-depth ideas.